Financial Attitude as a Mediating Variable for Financial Inclusion and Financial Literacy on The Financial Performance of MSMEs - Adibah Yahya; Denny Saputera; Taufik Hidayat; Rina Nurjanah (AFRE (Accounting and Financial Review), 2024)
This study aims to examine financial inclusion, financial literacy and financial attitudes towards the financial performance of MSMEs. Problems faced by MSMEs regarding financial management.Â  Factors that affect the financial performance of MSMEs include financial inclusion knowledge, financial literacy, and financial attitudes. The population of this research is MSMEs in Bekasi Regency. The research sample used a non-probability sampling method, namely quota sampling. Data processing techniques using PLS. The results showed that directly, financial inclusion and financial literacy had a significant positive effect on financial performance. However, financial attitudes have no effect on financial performance, besides that financial attitudes cannot mediate the effect of financial inclusion and financial literacy on financial performance. Financial literacy on financial performance.DOI: https://doi.org/10.26905/afr.v7i2.12685